Sistem Monitoring Arus dan Tegangan Pada Panel Surya 50Wp Berbasis IoT - Suoth, Verna Albert; Pandara, Dolfie Paulus; Kolibu, Hesky Stevy (Sam Ratulangi University, 2026)
The utilization of small-scale solar panels, particularly those with a capacity of 50 Wp, has become increasingly widespread in household systems and remote areas. However, the lack of adequate monitoring systems makes it difficult for users to identify actual panel performance, causing efficiency degradation to often go undetected at an early stage. This study aims to develop a current and voltage monitoring system for a 50 Wp solar panel based on the Internet of Things (IoT) that is capable of providing real-time performance data to support performance evaluation and more efficient energy management. The system was developed using current and voltage sensors, an ESP32 microcontroller, and a cloud-based IoT application for data visualization. The test results indicate that the system is able to monitor daily variations in current and voltage with good accuracy and stable data transmission. The measured output power of the solar panel ranges from 1 to 1.4 W, or approximately 2–3% of the nominal capacity, which is influenced by solar radiation intensity, panel temperature, and system losses. The proposed IoT-based monitoring system has proven effective in recording the actual performance of the solar panel and providing real-time information that is useful for performance evaluation and optimization of small-scale solar energy utilization.